2006
DOI: 10.1002/eat.20296
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in women with eating disorders: Problem of response inhibition, planning, or attention?

Abstract: These findings suggest that binge-eating behavior coincides with problems of response inhibition, whereas a risk-taking attitude may be a unique characteristic of individuals with BN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
150
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(190 citation statements)
references
References 23 publications
21
150
3
6
Order By: Relevance
“…Women with BN performed more poorly than healthy matched controls on all four inhibition tasks, indicative of cognitive disinhibition. This supports and extends previous findings of inhibitory dysfunction in BN (Kaye et al, 1995;Marsh et al, 2009;Rosval et al, 2006;Toner et al, 1987). The consistently poorer performance of the patient sample across tasks attests to the robustness of inhibitory deficiency in BN.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Women with BN performed more poorly than healthy matched controls on all four inhibition tasks, indicative of cognitive disinhibition. This supports and extends previous findings of inhibitory dysfunction in BN (Kaye et al, 1995;Marsh et al, 2009;Rosval et al, 2006;Toner et al, 1987). The consistently poorer performance of the patient sample across tasks attests to the robustness of inhibitory deficiency in BN.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Toner, Garfinkel and Garner (1987) showed that patients with bulimic symptoms made more errors than those with anorexic symptoms and healthy controls on the Matching Familiar Figures test, while Kaye, Bastiani and Moss (1995) reported that BN patients were faster to make their initial response on this inhibition measure than were AN patients. In contrast, Southgate, Tchanturia and Treasure (2008) Likewise, Rosval et al (2006) found that BN patients made more errors than AN patients and non-eating disordered controls on the go/no-go task, whereas Claes, Nederkoorn, Vandereycken, Guerrierri and Vertommen (2006) observed no differences among these participant groups on a similar measure, the stop-go task. In addition, Ferraro, Wonderlich and Jocic (1997) inferred cognitive disinhibition from a speed-accuracy trade-off in performance on the Symbol-Digit Modalities test.…”
mentioning
confidence: 93%
“…[6][7][8][9] Inhibitory control refers to the ability to suppress inappropriate and unwanted actions. 10 Impaired response inhibition in individuals with bulimic-type eating disorders is not limited to binge eating, but frequently includes several impulsive behaviours (e.g., excessive drinking, substance abuse), 11 suggesting a more general dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…También se ha señalado que en la AN de tipo purgativo y en la BN habría mayores niveles de impulsividad relacionada con la actividad motora y que en la BN habría una mayor tendencia a actuar de forma imprudente e incluso de forma peligrosa (22). De hecho, la impulsividad es un constructo multidimensional que implica aspectos cognitivos (planeamiento), atencionales y conductuales.…”
Section: Discussionunclassified
“…En cuanto a la primera hipótesis de presente trabajo, las correlaciones del EAT-40 con algunos ítems de la escala de Barratt (correspondientes a impulsividad motora y cognitiva) halladas en el presente estudio sugieren una vinculación entre la impulsividad y la conducta alimentaria que no solo aparece en pacientes con TCA (22), sino que pueden observarse en participantes no clíni-cos. Ello daría soporte a la hipótesis planteada.…”
Section: Discussionunclassified